2013
DOI: 10.1142/s1793292013500690
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as Tunable Stationary Phase Additive for Enantioseparation

Abstract: Graphene-based biosensor and chiral sensor have made significant progress in recent years. Because of the similarity of the optical enantiomers, enantioseparation is perhaps the most subtle to achieve. Developing more effectively chiral separation techniques based on graphene is highly desirable. Herein, pristine graphene was prepared and then applicated to assist resolution of two racemic drugs of propranolol and ofloxacin using thin-layer chromatography (TLC). In comparison with TLC chiral separation by only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In the past a few years, graphene oxide (GO) and graphene nanosheets have attracted tremendous interest in various applications such as photocatalysts, batteries, supercapacitors, sensors, pharmaceutical and environmental pollution management [4][5][6][7][8][9][10]. GO is an oxidized form of graphene in vigorous oxidation conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past a few years, graphene oxide (GO) and graphene nanosheets have attracted tremendous interest in various applications such as photocatalysts, batteries, supercapacitors, sensors, pharmaceutical and environmental pollution management [4][5][6][7][8][9][10]. GO is an oxidized form of graphene in vigorous oxidation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…GO is an oxidized form of graphene in vigorous oxidation conditions. After seminal works of B. C. Brodie on flake graphite in 1859, Hummers and his coworkers made some modifications on oxidation of graphite by use of H 2 SO 4 and KMnO 4 , which has been a basis of the present chemical methods for GO production [11]. GO is formed from graphene sheets with one atom in thickness and generally surrounded by polar functional groups (-OH, -COOH, epoxy groups) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, graphene and GO exhibit considerable potential in separation science [165] and has been used by several research groups for the enantiomeric separation of chiral molecules. For instance, Tu et al [106] reported the graphene assisted resolution of two racemic drugs propranolol and ofloxacin using pure d -(–)-TA as the chiral selector in TLC. Interestingly, computational simulations using density functional theory also showed the applicability of nanoporous graphene, when functionalized by a chiral bouncer molecule [171].…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%
“…The enantioselective sensing in electrochemical techniques is due to the enantioselective interaction between a chiral selector and the chiral analyte . Chiral selectors with different spacial arrangements of functional groups including amino, hydroxyl, carbonyl, phenyl, and carboxyl groups are responsible for chiral recognition characteristic of the modified electrode . The presence of 9 chiral centers as well as possessing the hydroxyl, fluorine, and carbonyl groups with hydrogen bonding capability can contribute to chiral recognition ability of BMZ (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…18 Chiral selectors with different spacial arrangements of functional groups including amino, hydroxyl, carbonyl, phenyl, and carboxyl groups are responsible for chiral recognition characteristic of the modified electrode. 19 The presence of 9 chiral centers as well as possessing the hydroxyl, fluorine, and carbonyl groups with hydrogen bonding capability can contribute to chiral recognition ability of BMZ (Scheme 1). In spite of BMZ chirality and its enantio-recognition potentiality, there was no report on using of BMZ as chiral selector.…”
Section: Introductionmentioning
confidence: 99%